2021
DOI: 10.1002/ajhb.23629
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genetic variation in human bioenergetics, adaptation, and adult disease

Abstract: Objectives Mitochondria are critical for the survival of eukaryotic organisms due to their ability to produce cellular energy, which drives virtually all aspects of host biology. However, the effects of mitochondrial DNA (mtDNA) variation in relation to disease etiology and adaptation within contemporary global human populations remains incompletely understood. Methods To develop a more holistic understanding of the role of mtDNA diversity in human adaptation, health, and disease, we investigated mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 242 publications
(329 reference statements)
0
2
0
Order By: Relevance
“…Mitochondria play a crucial role in cellular homeostasis and function as the powerhouse of the cell, involved in metabolism and signal transduction [16,17]. Studies have shown that mitochondria and the endoplasmic reticulum (ER) interact through mitochondria-associated ER membranes (MAMs) to maintain cellular balance [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria play a crucial role in cellular homeostasis and function as the powerhouse of the cell, involved in metabolism and signal transduction [16,17]. Studies have shown that mitochondria and the endoplasmic reticulum (ER) interact through mitochondria-associated ER membranes (MAMs) to maintain cellular balance [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are unique organelles among all intracellular organelles because they contain their own DNA. Through the migration, isolation, and evolution of humans, mitochondrial DNA (mtDNA) formed a wide range of mitochondrial genome polymorphisms [ 7 ]. Mitochondria are complex organelles encoded both by nuclear and mtDNA [ 8 ].…”
Section: Introductionmentioning
confidence: 99%